Lifestyle Analysis, Pocket Money and Financial Literacy on Consumtive Behavior - Julita Julita; Rizky Aditya; Rizky Rizky (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2023)
This study aims to determine how the influence of lifestyle, pocket money and financial literacy on consumptive behavior partially and simultaneously in students of the Faculty of Economics and Business, University of Muhammadiyah North Sumatra. This research is a quantitative research with data collection using a questionnaire. The population in this study were students of the Department of Management, Faculty of Economics and Business, University of Muhammadiyah North Sumatra in 2018. The sample in this study amounted to 100 respondents. The sampling technique used is simple random sampling method. Primary data processing using Statistical Package for Social Science (SPSS) analysis technique with multiple regression analysis method. The results of this study conclude that individually (partial) lifestyle on consumptive behavior has a positive and significant effect, pocket money and financial literacy have no significant effect on consumptive behavior while simultaneously lifestyle, pocket money and financial literacy have a positive and significant effect on consumptive behavior.